PNPLA3/adiponutrin functions in lipid droplet formation. (17th April 2013) - Chamoun, Zeina; Vacca, Fabrizio; Parton, Robert G.; Gruenberg, Jean
Abstract Background Information In animals, adipose tissue contains the main energy store as lipid droplets (LDs) composed of esterified cholesterol (CE) and triacylglycerol (TAG) enveloped in a mono‐layer of phospholipid and decorated by a coat of proteins. Upon increased energy demand, dedicated lipases hydrolyse TAG stepwise into free fatty acids that are released in circulation and made available to peripheral tissue. In case of aberrant caloric load, TAGs are deposited into non‐adipocyte tissues, primarily liver cells. For instance, non‐alcoholic fatty liver disease (NAFLD) is a common chronic disorder characterised by an excess of TAG in the liver of patients regardless of their susceptibility to obesity, diabetes or exposure to alcohol. Several independent linkage studies have associated NAFLD with a non‐synonymous variant of patatin‐like phospholipase domain‐containing 3 (PNPLA3/adiponutrin) encoding an isoleucine to methionine substitution at position 148 (I148M) (see Cohen et al., 2011 for review). However, the mechanism by which a variation in PNPLA3 gives susceptibility to NAFLD is not known, primarily because the physiological role of PNPLA3 still needs to be elucidated. Results We have identified PNPLA3 in a screen for genes upregulated by intracellular lipid accumulation. We investigated the sub‐cellular distribution and potential function of PNPLA3 in fibroblast‐like cells supplemented with lipids. We demonstrate that PNPLA3 is targetted to LDs in a process that requires an intact Brummer box domain, which is conserved in the patatin‐like phospholipase family. We show that increased levels of the NAFLD‐linked PNPLA3 isoform leads to larger LDs, whereas decreased levels of PNPLA3 had the opposite effect. Interestingly, however, PNPLA3 induced a reduction in LD size upon co‐expression with ABDH5/CGI‐58, an activator of the TAG lipase PNPLA2, which is the closest homolog of PNPLA3. By investigating LD populations according to their size and composition, we show that perturbing intracellular lipid trafficking drastically modifies LD nature. Conclusions Taken together, our results suggest that PNPLA3 exhibits a dual function in LD metabolism, and that it participates in the restoration of lipid homeostasis upon aberrant intracellular lipid accumulation.